Effects of irbesartan on phenotypic alterations in monocytes and the inflammatory status of hypertensive patients with left ventricular hypertrophy - Jingsi Zhang; Lina Yang; Yanchun Ding (BMC Cardiovascular Disorders, 2021)
Abstract Background Circulating monocytes and tissue macrophages play complex roles in the pathogenesis of hypertension and the resulting target organ damage. In this study, we observed alterations in the monocyte phenotype and inflammatory state of hypertensive patients with left ventricular hypertrophy (LVH) and studied the effects of irbesartan in these patients. This study might reveal a novel mechanism by which irbesartan alleviates LVH, and it could provide new targets for the prevention and treatment of hypertensive target organ damage. Methods CD163 and CD206 expression on monocytes and IL-10 and TNF-α levels in the serum of hypertensive patients with or without LVH and of healthy volunteers were detected. Furthermore, we treated monocytes from the LVH group with different concentrations of irbesartan, and then, CD163, CD206, IL-10 and TNF-α expression was detected. Results We found, for the first time, that the expression of CD163, CD206 and IL-10 in the LVH group was lower than that in the non-LVH group and healthy control group, but the TNF-α level in the LVH group was significantly higher. Irbesartan upregulated the expression of CD163 and CD206 in hypertensive patients with LVH in a concentration-dependent manner. Irbesartan also increased the expression of IL-10 and inhibited the expression of TNF-α in monocyte culture supernatants in a concentration-dependent manner. Conclusions Our data suggest that inflammation was activated in hypertensive patients with LVH and that the monocyte phenotype was mainly proinflammatory. The expression of proinflammatory factors increased while the expression of anti-inflammatory factors decreased. Irbesartan could alter the monocyte phenotype and inflammatory status in hypertensive patients with LVH. This previously unknown mechanism may explain how irbesartan alleviates LVH. Trail registration The study protocols were approved by the Ethical Committee of the Second Affiliated Hospital of Dalian Medical University. Each patient signed the informed consent form.